Features of the analysis of economic activity in the organizations of agro-industrial complex - Андыбаева, Г. (Journal of Economic Research & Business Administration, 2017)
Results of work of the entities of agricultural industry considerably depends on a production condition. Therefore the economic analysis begins with studying of climatic conditions, the size of a production orientation, level of intensifications of production and its efficiency. Only taking into account specific circumstances it is possible to estimate objectively results of activities of the entity and to determine it ways of further development. Conditions of production can be divided into three groups: climatic conditions, economy location, economic situation of production. Each of these groups is characterized by the corresponding system of indicators. In article features of the economic analysis of activities of agricultural organizations and each feature which enters into group are divided into two groups it is specifically shown. At the same time the acceptances and methods applied in the analysis of results of works of agricultural industry, indicators of studying of level of an intensification of production are determined.